Language Ethics in the Digital Era: Between Freedom of Expression and Social Responsibility - Susanti Fajariyah; Istigfariyah Ramadhani; Eka Fitriyani; Fahrur Rozi; Moh. Zainollah (Jurnal Multidisiplin Sahombu, 2025)
Language ethics in the digital era are a crucial moral foundation for building a civilized communication civilization. Social media, as a modern public space, has shifted the function of language from a mere communication tool to a determinant of image, opinion, and social identity. However, freedom of expression is often misused as a means of spreading hate speech, sarcasm, body shaming, and hoaxes. Various studies (Rozak et al., 2023; Wijayanti et al., 2022; Ramdlanah, 2022) show that the crisis in language ethics is correlated with low digital literacy, moral degradation, and a loss of empathy in online interactions. Polite language reflects not only individual character but also national dignity. Therefore, strengthening digital literacy and language ethics education need to be integrated into the national education system as an effort to foster a civilized digital character. Amidst viral culture and the post-truth era, language ethics serves as a moral filter to maintain truth and social harmony. In conclusion, language ethics is not simply a matter of politeness, but a reflection of the nation's moral, social, and spiritual values, determining the direction of Indonesia's digital civilization.